ATP-dependent interplay between local and global conformational changes in the myosin motor - Kiani, Farooq Ahmad; Fischer, Stefan (Cytoskeleton, 2016)
The ATPase active site of myosin is located at the core of the motor head. During the Lymn-Taylor actomyosin contractile cycle, small conformational changes in the active site upon ATP binding, ATP hydrolysis and ADP/Pi release are accompanied by large conformational transitions of the motor domains, such as opening and closing of the actin binding cleft and the movement of lever arm. Here, our previous computational studies of myosin are summarized in a comprehensive model at the level of atomic detail. Molecular movies show how the successive domain motions during the ATP induced actin dissociation and the recovery stroke are coupled with the precise positioning of the key catalytic groups in the active site. This leads to a precise timing of the activation of the ATPase function: it allows ATP hydrolysis only after unbinding from actin and the priming of the lever arm, both pre-requisites for an efficient functioning of the motor during the subsequent power stroke. These coupling mechanisms constitute essential principles of every myosin motor, of which the ATP-site can be seen as the central allosteric control unit. © 2016 Wiley Periodicals, Inc.
Gesehen am 11.05.2020